2008
DOI: 10.1007/s12028-008-9163-y
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressors and Propofol Infusion Syndrome in Severe Head Trauma

Abstract: Awareness and early recognition of PRIS in critically ill neurosurgical patients on vasopressors and daily screening for creatine kinase elevation, unexplained acidosis, or electrocardiographic changes may reduce the incidence and case-fatality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…The combination of a high dose of propofol with vasopressor use, and high endogenous levels of catecholamines in the myocardium, may increase the risk for developing PRIS in patients with severe head trauma [7]. During stress metabolism, catecholamines serve as a major trigger for lipolysis, leading to accumulation of free-fatty acids, which is another risk factor for developing PRIS [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a high dose of propofol with vasopressor use, and high endogenous levels of catecholamines in the myocardium, may increase the risk for developing PRIS in patients with severe head trauma [7]. During stress metabolism, catecholamines serve as a major trigger for lipolysis, leading to accumulation of free-fatty acids, which is another risk factor for developing PRIS [5].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is poorly understood but clinical manifestations include cardiac failure, hypotension, metabolic acidosis, renal failure, and rhabdomyolysis [4,5]. Occurrence is generally associated with higher propofol dosages (N 4 mg/kg/hr), prolonged application (N 48 hrs), and in patients with neurological or neurosurgical diseases [2,6,7]. A case of fatal PRIS in a patient receiving the drug at a moderate dosage is presented.…”
Section: Introductionmentioning
confidence: 99%
“…16 Vasopressors. In their review of neurological ICU patients, Smith and colleagues 17 reported a relationship between the use of vasopressors and the development of propofol infusion syndrome. They suggested that this effect could be caused by the action of propofol and vasopressors on the heart.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Arrhythmias including atrial fibrillation, bradycardia, bundle branch block, ventricular tachycardia and asystole have also been reported ( Table 2) [17]. The incidence of PRIS is unknown as no formal registry exists to record patients who develop the syndrome, but since the first case reports in 1992, more than 35 children and approximately 40 adults have demonstrated signs and symptoms suggestive of PRIS [18][19][20][21][22][23][24][25]. Following discontinuation of the propofol infusion, treatment of the syndrome is primarily supportive and the associated mortality is high.…”
Section: Propofolmentioning
confidence: 99%